Economic Status, Parenting Patterns, and Duration of Gadget Use Influence the Social Development of Group B Children - Milla Ignatesia Ginting; Aslamiah; Novitawati (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
In the era of globalization, more and more children are being influenced by technological advances. One of the technological advances that children like is gadgets. The introduction of gadgets to children usually starts with parents and family showing videos or games on the gadget in the hope that the child will stop crying and not be fussy. This research aims to analyze and describe parents' economic status, parenting patterns, gadget use duration, and early childhood social development. This research method is descriptive quantitative. The total sample was 158 parents. The data collection instrument uses a questionnaire that meets the validity and reliability test requirements. Data analysis to test hypotheses uses path analysis. Based on the results of this research, it was found that first, there is a direct relationship between economic status and children's social development. Second, parenting styles and children's social development. Third, the duration of gadget use depends on the child's social development. Fourth, economic status and duration of gadget use. Fifth, parenting patterns and duration of gadget use. Sixth, economic status through the duration of gadget use and children's social development. Seventh, economic status through the duration of gadget use and children's social development. It was concluded that there was a relationship between economic status, parenting patterns, and duration of gadget use with the social development of early childhood.